Application of Table 100 Media in Addition and Subtraction Learning to Improve Math Learning Outcomes - Inayatus Sangadah; Muh Ngali Zainal Makmun; Nurul Aisyah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research uses a type of quantitative research with a quasi-experimental approach by using the 100 table media to improve math learning outcomes. This study used 100 learning table media to improve math learning outcomes. The quantitative approach used in this research is a type of quasi experiment. This study uses the table 100 media as the independent variable and student learning outcomes as the dependent variable. In this study, 20 students were used as samples. Observation, interview, test, survey, and documentation are the methods used to collect data. The steps of proposing hypotheses and testing normality are the data analysis procedures. The paired sample t test (t-test) resulted in Sig. (2-tailed) 0.02 in the experimental class, in accordance with the results of hypothesis testing. In contrast, the control class had a Sig. (2-tailed) of 0.01. The findings of the 2-tailed sig value can be compared with hypothesis testing if the sig (2-tailed) value is between 0.01 and 0.02. With the assumption that the 2-tailed sig value is greater than 0.05, the hypothesis is not rejected if it is less than 0.05. This shows that the math learning outcomes of grade II students of MI Ma'arif NU 6 Karyamukti are influenced by the table 100 media. The normality test shows that the Experiment class has a significance value of 0.018 and 0.088 before and after the test, while the Control class has a significance value of 0.200 and 0.135. If the p-value is less than 0.05, it can be concluded that the data follows a normal distribution.